Vehicle Monitoring System with Geofencing Capability - Jospine, Alendra; Muhammad Audah, Lukman Hanif; Hamzah, Abdul Wahhab Essa; Qasim, Hamzah Hadi (Journal of Electronic Voltage and Application, 2020)
Global Positioning System (GPS) is a technology used to determine the position of a specific object by using the concept of a Global Navigation Satellite System (GNSS). The concept of geofencing known as the technology that used the GPS technology to design the boundary on a specific area where once the vehicle crossed the geofence area, it will trigger the system and send notifications either email or SMS. One of the main purposes of GPS is to track the location of a device, object or vehicle and it can be displayed on the map. Currently, the technology of monitoring the location of the vehicle still not being implemented to a certain company. Therefore, this project presents the vehicle monitoring system with geofencing capability where the purpose of this project is to monitor the location of the vehicle especially for Universiti Tun Hussein Onn Malaysia (UTHM). Furthermore, this system provides a monitoring system on a real-time mode for the vehicle which also can be viewed on the smartphone. It also gives a notification once the vehicle is out of the geofence area. The component required for this system is Arduino Mega 2560 and FONA808 shield attached with GPS, GSM and Li-poly battery and the application needed to display the current location of the vehicle is Blynk App. Blynk App, will display information such as latitude, longitude and the map. The administrator of managing the vehicle is able to access the application via smartphone as long as there is internet connection. Hence, this system has been tested once the vehicle exits and enters the geofence area and the result shows the correct location of the vehicle along with email notifications.